Asset Tracing on a Distributed Multimedia Production Environment - Rui Grandão Rocha (2016)
n a multimedia production environment where multiple users work with assets present in a dis- tributed file system, assets can range from the original video captured on the field to the ones that will be broadcasted later, after production is finished. These assets can be either single video files or complex packages containing multiple files and custom metadata. In these types of environ- ments it is important to know, at any given point in time, where the files are, as well as who is working on them and how long each task is taking. In such scenarios, problems such as knowing if a given file is present in an asset after production, tracing the assets so that we know the path they took throughout the network or even keeping track of the files when they change identity, need to be solved. The proposed solution aims to tackle the problem present in tracing the path that these assets took while keeping up with their identities and showing the user this information in a simple yet meaningful way. We do this by using graph based databases to maintain the connection between the different paths that the assets took, while maintaining a list of identities that each asset had throughout the process so that when assets change we still know which one they are. Solutions like these are valuable not only in the multimedia production context but also in other areas such as in electronic commerce and distribution. Enterprises like eBay are using graph based technologies to enhance their delivery service routing, making it possible that products are delivered in the same day as ordered. This solution has also the added value of being able to provide insightful information to rec- ommendation systems and intelligent search engines through an API that will give them access to the information we gather, which will be useful to them as they can use it to provide better results for its users.